2018
DOI: 10.1021/acscatal.8b01799
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Methods for Assessing Kinetic Factors in the Reduction of CO2 to Formate: Implications for Improving Electrocatalyst Design

Abstract: Thermochemical insights are often employed in the rationalization of reactivity and in the design of electrocatalysts for CO2 reduction reactions targeting C–H bond-containing products. This work identifies experimental methods for assessing kinetic aspects of reactivity. These methods are illustrated using [Fe4N­(CO)12]−, which produces formate from CO2 at −1.2 V versus SCE in either a MeCN/H2O solvent (95:5) or pH 6.5 buffered water. Elementary rates for each reaction step are identified along with the rate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…The product distribution could be tuned in a controlled manner by modulating the applied potential, affording syngas mixtures with a CO : H 2 ratio of 1 : 1 or 1 : 2 at more negative potentials, likely due to the partial contribution of the less CO 2 RR selective Ni I/0 wave. 261 The majority of the non-heme Fe electrocatalysts studied for CO 2 RR displayed high or moderate faradaic efficiencies for formate production, including a highly selective iron carbonyl cluster catalyst 69,262,263 and Fe complexes with bipyridinecontaining Schiff base ligands, 264,265 phenanthroline derivatives 266 or macrocyclic nitrogen platforms. 260 Recently, a series of Fe II complexes supported by polydentate bipyridyl-based platforms bearing different functional groups in the second coordination sphere, were explored for CO 2 RR.…”
Section: Non-macrocyclic Tetradentate Nitrogen Ligandsmentioning
confidence: 99%
“…The product distribution could be tuned in a controlled manner by modulating the applied potential, affording syngas mixtures with a CO : H 2 ratio of 1 : 1 or 1 : 2 at more negative potentials, likely due to the partial contribution of the less CO 2 RR selective Ni I/0 wave. 261 The majority of the non-heme Fe electrocatalysts studied for CO 2 RR displayed high or moderate faradaic efficiencies for formate production, including a highly selective iron carbonyl cluster catalyst 69,262,263 and Fe complexes with bipyridinecontaining Schiff base ligands, 264,265 phenanthroline derivatives 266 or macrocyclic nitrogen platforms. 260 Recently, a series of Fe II complexes supported by polydentate bipyridyl-based platforms bearing different functional groups in the second coordination sphere, were explored for CO 2 RR.…”
Section: Non-macrocyclic Tetradentate Nitrogen Ligandsmentioning
confidence: 99%
“…[18][19][20][25][26][27][28][29][30] Product selectivity in CO 2 reduction is one of the most important issues to be addressed. [31][32][33][34][35][36] While in general molecular catalysis is limited to 2-electron reduction leading to formic acid and/or carbon monoxide, a major competing reaction is the reduction of protons into dihydrogen. 10,37 Optimization of the catalytic systems thus requires a better understanding of the factors which would limit the hydrogen evolution reaction.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Wellknown examples are Ru-polypyridyl, Mn(bpy)(CO) 3 and Rh(bpy=2,2′-bipyridine)(Cp*=pentamethylcyclopentadienyl) complexes, followed recently by Co(diphosphine)(Cp) complexes 30 and Fe-carbonyl clusters. [32][33][34][35] These systems most often give a mixture of HCOOH and H 2 , but the control of their selectivity has not been addressed in details.…”
Section: Introductionmentioning
confidence: 99%
“…Equation 3 applies to the determination of rate constants for stoichiometric chemical steps immediately following an ET event under purely kinetic conditions. However, the method has also proven valuable to investigate the rate of chemical steps in more complicated mechanistic pathways (such as ECEC or ECCE catalysis, Scheme 2), [16,28,29,37] when the substrate concentration is kept low so that no catalytic turnover is observed on the timescale of the CV experiment. To minimize turnover we collected CV's at varied scan rate, 0.1 to 0.9 Vs À 1 , on solutions containing low concentrations of AnsdH + , 0.2 mM, and of 1 2À , 0.15 mM, and the 1 3À /4À redox couple remained reversible in this study.…”
Section: Resultsmentioning
confidence: 99%
“…[3,15] The reactivity of molecular electrocatalysts has also been shown to change with reaction conditions: two studies demonstrated that water as a solvent stabilizes transition states for hydride transfer to CO 2 and in those cases HER was effectively suppressed. [16,17,18] MCCs are atomically defined nanomaterials and this enables their precise characterization using molecular tools to understand elementary reaction steps and physical properties while harnessing many of the desirable reactivity characteristics of heterogeneous or nanomaterial electrocatalysts. Recent work demonstrated that the many metal-metal bonds in a cobalt carbonyl cluster statistically enhance PT rates to afford an overall turnover frequency (TOF) for HER of k obs = TOF = 1 × 10 8 s À 1 using [Co 13 C 2 (CO) 24 ] 4À (2 4À ) as catalyst with an applied potential of À 0.86 V vs. SCE (η = 760 mV and k obs is the observed rate constant).…”
Section: Introductionmentioning
confidence: 99%